139k views
1 vote
3n – 5 = 6(n + 2)
With work plz

2 Answers

4 votes

Answer:

n≈-5.67

Explanation:

3n-5=6(n+2)

3n-5=6n+12

3n=6n+17

-3n=17

n≈-5.67

User Clay Fowler
by
5.0k points
6 votes

Answer:

n = -17/3

Explanation:

3n -5 = 6(n+2)

First start by distributing the 6 on the right side:

3n-5 = 6n +12

Then combine common factors. Start with the coefficients. Add 5 to both sides:

3n = 6n +17

Then subtract 6n from both sides:

-3n = 17

Finally, isolate the variable by dividing -3 from both sides:

n = -17/3

User Wuliwong
by
5.7k points